Ethnicity and Gender in the Beat Generation: Jack Kerouac and the Other Woman - Encarnación-Pinedo, Estíbaliz (International Journal of English Studies, 2022)
Pivoting around the contrast between Jack Kerouac’s On the Road (1957) and Tim Z. Hernandez’s Mañana Means Heaven (2013), this article reopens debates about ethnic appropriation and rhetorical control in the Beat Generation. More specifically, it sets out to investigate whether the textual strategies used in Mañana Means Heaven allow ethnic minorities to escape the discursive control exerted by On the Road. Keeping in mind that Hernandez’s text acts as a counter-discursive text to Kerouac’s representation of Bea Franco (aka “the Mexican girl”) this article analyzes the different dialogues Mañana Means Heaven necessarily establishes with On the Road, which often include alliances as well as points of departure.